The Position of Women’s Political Rights in Arab Constitutions and International Conventions - Al-Shabatat , Mohammed Ali (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to shed light on one of the most important rights of women that have struggled for decades to obtain that right that enables them to participate in politics through candidacy and elections, assuming public positions in the State and joining political parties, but as a result of her constant struggle to obtain that right, which was recognized by many international covenants and treaties, they varied in terms of the guarantee that the constitutions of countries, in general, and those of Arab countries in particular.